Investigating the effect of SGLT2 inhibitors on cardiovascular related health status in HFmrEF and HFpEF: systematic review and meta analysis - Kusi-Yeboah, Tabitha; Gianfrancesco, Isaac; Jabbar, Muzammil Arif Din Abdul; Collins, Phoebe; Bally, Dalton James; Thornton, Juliet; Williams, Kieran; Ishola, Ayoola; Hong, Lucy; Toong, Ping Jing; Wickramarachchi, Milindu (Frontiers in Cardiovascular Medicine, 2025)
Background and aimsSodium-glucose co-transporter 2 inhibitors (SGLT2i) have emerged as an integral component of heart failure management, with evidence supporting their benefits across a broad spectrum of ejection fractions. However, their impact on quality of life (QoL) in patients with heart failure with mildly reduced (HFmrEF) and preserved ejection fraction (HFpEF) remains underexplored. This systematic review and meta-analysis aim to evaluate the effects of SGLT2i on QoL compared to standard therapy in these patient populations.MethodsA systematic search of PubMed, Cochrane, and EMBASE databases was conducted for randomized controlled trials (RCTs) published in English that assessed the clinical outcomes of SGLT2i in HFpEF and HFmrEF up to January 23, 2024. Two independent reviewers evaluated the risk of bias for eligible studies. A random-effects model was used for meta-analysis. The primary outcomes of interest were changes in the Kansas City Cardiomyopathy Questionnaire (KCCQ) score and 6 Minute Walk Test Distance (6MWTD).FindingsA total of 7 RCTs comparing KCCQ score in HFpEF and HFmrEF in participants receiving SGLT2i vs. placebo, and 3 RCTs comparing 6MWTD in HFpEF and HFmrEF in participants receiving SGLT2i vs. placebo were included in the systematic review. Overall SGLT2i was associated with an increase in KCCQ-TSS score (MD = 2.28, 95% CI 1.94–2.63, I2 = 0%) and 6MWTD (MD = 13.52, 95% CI 1.70–25.34, I2 = 62%).InterpretationThese findings suggest that SGLT2i not only confer cardiovascular benefits but also enhance patient-reported health status, reinforcing their role as a valuable adjunct to standard heart failure therapy in HFmrEF and HFpEF.